Pollen morphology of some Tanacetum L. (Asteraceae) taxa and its systematic value - Kursat, Murat; Celtik, Ismail; Baser, Birol; Ozbey, Fahrettin; Emre, Irfan (Tubitak Scientific & Technological Research Council Turkey, 2023)
Pollen grains of 24 Tanacetum taxa from Turkiye were examined by light (LM) and scanning electron microscopy (SEM). Detailed pollen morphological characteristics are provided for these taxa. According to the 24 analyzed taxa, T. parthenifolium has the smallest pollen grains, and T. aurem var. aurem possesses the largest ones. The basic shape of the pollen grains in most taxa is oblate spheroidal. However, suboblate pollen grains are recorded for T. balsamitoides, T. aurem var. aurem, and T. tomentellum. The polar axis ranges from 16.56 to 26.14 mu m, and the equatorial diameter ranges from 17.64 to 30.12 mu m in this study. The grains are trizonocolporate, and exine sculpturing is echinate in all taxa. The ornamentations between spines are reticulate, microreticulate, perforate, microperforate, perforate-granulate, microperforate-granulate, rugulate-granulate, and rugulate-perforate. Pollen morphological characteristics of the taxa studied are compared and discussed on the basis of taxonomical concepts. The unweighted pair group approach with arithmetic mean was also employed to assess the morphological differentiation of the pollen, and four types were identified in the dendrogram created from the studied data using this method. In addition, principal component analysis confirms the dendrogram results. In some cases, the pollen characters are useful in distinguishing the taxa.
Keywords: Asteraceae; cluster analysis; pollen morphology; Tanacetum; Turkiye